Hallmarks of Hunds coupling in the Mott insulator Ca2RuO4 - D. Sutter (Nature Portfolio, 2017)
Detailed knowledge of the low-energy electronic structure is required to understand the Mott insulating phase of Ca2RuO4. Here, Sutter et al. provide directly the experimental band structure of the paramagnetic insulating phase of Ca2RuO4and unveil the electronic origin of its Mott phase.